Pengaruh Pendidikan Karakter, Budaya Organisasi, dan Peran Orangtua Terhadap Mutu Pendidikan SMP Muhammadiyah Se-Kota Batam - Mashudi; Elli Widia; Sardjijo (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
This study is intended to analyze the influence of organizational culture character education, and the role of parents on the quality of education at Muhammadiyah Middle Schools in Batam City. The variables studied were character education (X1), organizational culture (X2), parental roles (X3), and quality of education (Y). A quantitative approach with a correlational design was used in the investigation with a non-probability sampling technique (census) of 119 respondents. Questionnaires and documentation were used for data collection. Descriptive statistical analysis, and multiple linear regression were used for data analysis. The results of multiple regression analysis obtained the equation for the quality of education (Y) = 05.830 + 0.366X1 + 0.758X2 +0.037X3. The results of multiple regression analysis show that the organizational culture variable has a greater value in influencing the quality of education. F test results obtained Fcount > Ftable that is 134,941 > 2,05. The conclusion is that the variables of character education, organizational culture, and the role of parents simultaneously and significantly impact the quality of education at Muhammadiyah Middle Schools in Batam City.